The anti-aggregating effect of BAY 41-2272, a stimulator of soluble guanylyl cyclase, requires the presence of nitric oxide - Roger, Séverine (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: The purpose of the present study was to determine whether a stimulator of soluble guanylyl cyclase, BAY 41-2272, inhibits platelet aggregation and to clarify its interaction with nitric oxide (NO). EXPERIMENTAL APPROACH: Blood was collected from anaesthetized Wistar Kyoto rats. The aggregation of washed platelets was measured and the production of cAMP and cGMP was determined. KEY RESULTS: In adenosine 5′-diphosphate (ADP)-induced platelet aggregation, the anti-aggregating effects of BAY 41-2272, nitroglycerin, sodium nitroprusside and DEA-NONOate were associated with increased levels of cGMP while that of beraprost, a prostacyclin analogue, was correlated with an increase in cAMP. 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ) prevented the effects of BAY 41-2272 and that of nitroglycerin and sodium nitroprusside, but only inhibited the increase in cGMP produced by of DEA-NONOate. Hydroxocobalamin, an NO scavenger, inhibited the effects of the three NO donors and BAY 41-2272 but did not affect those of beraprost. ADP-induced aggregation and the effects of BAY 41-2272 were not affected by L-nitroarginine. A positive interaction was observed between BAY 41-2272 and the three NO donors. BAY 41-2272 potentiated also the anti-aggregating effects of beraprost, and again this potentiation was inhibited by hydroxocobalamin. CONCLUSIONS AND IMPLICATIONS: Inhibition of platelet aggregation by BAY 41-2272 requires the reduced form of soluble guanylyl cyclase and the presence of NO. The positive interaction observed between BAY 41-2272 and various NO donors is qualitatively similar whatever the mechanism involved in NO release. Furthermore, a potent synergism is observed between BAY 41-2272 and a prostacyclin analogue, but only in the presence of NO.